Akut lenfoblastik lösemili çocuk hastaların beyin omurilik sıvısı oksidan/antioksidan seviyeleri - (:unkn) unknown (My University, 2014)
Amaç: Akut lenfoblastik lösemili çocuk hastalarda tedavinin beyin omurilik sıvısında (BOS) antioxidant ve oksidan seviyelerini araştırmak. Materyal ve Metod: 24 (15 erkek 9 kız) yeni tanı almış hastaların tanı anında, remisyon indüksiyon, güçlendirme, idame ve tedavi sonunda BOS seruloplazmin ferroksidaz aktivitesi, total tiyol, lipid hidroperoksit (LOOH), ve total oksidant seviyeleri (TOS) çalışıldı. Çalışmaya 19 çocuk (10 erkek 9 kız) (kontrol) olarak alındı. Bulgular: İ lk tanıda ALL grubunda kontrol grubuna göre sırasıyla, ortalama ferrokisdaz aktivitesi (50.2 ± 10.4 U/L ve 30.3 ± 7.9 U/L), total tiyol (0.34 ± 0.02 µmol/L ve 0.18 ± 0.01 µmol/L), LOOH (6.5 ± 1.9 µmol/L ve 5.3 ± 0.8 µmol/L), ve TOS (9.3 ± 4.3 µmol HOequiv./L ve 6 ± 1.5 HOequiv./L) bulundu ( P < 0.05). 22 22 Ferroksidaz aktivitesi tüm tedavi süresince yüksek seyrettiği, total tiyol seviyesinin ise tedavinin ilk 80 haftasında yüksek kaldığı daha sonra azlamaya başladığı, total oxidant seviyenin ise idamenin 7 haftası ile 120 haftasında düşüşler gösterdiği saptandı. Sonuç: ALL'li çocuk hastaların BOS oksidan stresi ve antioksidanları yüksek seviyededir ve tedavi süresince bu yükseklik devam etmektedir.

Objective: To assess the effect of leukemia therapy on the cerebrospinal fluid (CSF) antioxidant and oxidant status in children with acute lymphoblastic leukemia (ALL). Material and Method: Twenty-four consecutive children (15 boys and 9 girls) newly diagnosed with ALL were enrolled in the study. CSF concentrations of ceruloplasmin ferroxidase activity, total thiol group, lipid hydroperoxide (LOOH) and total oxidant status (TOS) were evaluated at diagnosis, remission induction, consolidation, continuation, and the end of the continuation. Nineteen children (10 boys and 9 girls) were enrolled as a reference group. Results: The study group at diagnosis had significant higher mean ferroxidase activity (50.2 ± 10.4 U/L and 30.3 ± 7.9 U/L), total thiol (0.34 ± 0.02 µmol/L and 0.18 ± 0.01 µmol/L), LOOH (6.5 ± 1.9 µmol/L and 5.3 ± 0.8 µmol/L), and TOS (9.3 ± 4.3 µmol HOequiv./L and 6 ± 1.5 HOequiv./L) levels compared with the 22 22 references, respectively ( P < 0.05).. Ferroxidase activity remained elevated during the entire treatment course. Total thiol levels stayed elevated from diagnosis to week 80 of ALL treatment and significantly decreased thereafter. LOOH levels were progressively increased to week 80 of the treatment course. TOS levels were progressively decreased two times at continuation week 7 and end of the treatment. Conclusions: Our data indicate that CSF oxidative stress and antioxidants are higher at diagnosis, significant changes to be during therapy, and is already high at the end of therapy in children with ALL.
Cerebrospinal fluid oxidant/antioksidant status in children with acute lymphoblastic leukemia
Keywords: Hematoloji; Genel ve Dahili Tıp; Tıbbi Araştırmalar Deneysel; Pediatri